Trade Costs - Anderson, James E; van Wincoop, Eric (Journal of Economic Literature, 2004)
This paper surveys the measurement of trade costs: what we know and don't know but may usefully attempt to learn. Partial and incomplete data on direct measures of costs go with inference on implicit costs from trade flows and prices. Total trade costs in rich countries are large. The ad valorem tax equivalent is about 170 percent when pushing the data hard. Poor countries face even higher trade costs. There is a lot of variation across countries and across goods within countries, much of which makes economic sense. In our survey, theory provides interpretation and perspective and suggests improvements for the future. Some new results are presented to properly apply and interpret gravity theory and handle aggregation.